Psychological Disorders and Ecological Factors Affect the Development of Executive Functions: Some Perspectives - Zebdi, Rafika; Goyet, Louise; Pinabiaux, Charlotte; Guellaï, Bahia (Frontiers in Psychiatry, 2016)
The links between deficits in executive functions (EF) (e.g., mental flexibility, inhibition capacities...), and some psychological disorders (e.g., anxiety and depressive disorders) has been investigated in the past decades or so. Observations evidenced that some deficits in working memory, planning, and mental flexibility were highly correlated with anxiety and depressive disorders. The majority of studies focused on adults’ population, whereas it seems important to adopt a developmental perspective to fully understand the dynamic of these EF/psychological disorders relations. We suggest two axis on which to focus in future research: (i) relations between EF and anxiety traits through development; and (ii) the possible role of external factors such as parent-child relationships on the development of EF.